Realizing Economic Independence of Housewives through the Provision of Business Model Canvas Education - Beatrix Adelaide Herijanto; Bill Smith Sayuti; Sri Natasya Br Sitepu (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2024)
The empowerment program for housewives in Glagaharum village aims to address the lack of business knowledge among women who have sewing skills. Through the provision of education on the Business Model Canvas, it is expected that the women participating in this training can independently and effectively design their own businesses. This activity begins with a pre-test given to 8 people followed by the process of identifying the value proposition of each participant, and then an explanation of each element in the Business Model Canvas such as customer segments, value propositions, distribution channels, customer relationships, key resources, key activities, key partners, revenue streams, and cost structure. The results of this program can be seen through the post-test results, which show an improvement in scores compared to the pre-test. Additionally, the participants were able to design and organize their own business models using Business Model Canvas during the meeting. Therefore, it can be concluded that this activity shows an increase in the participants' understanding of business knowledge, and it is hoped that the participants can design their business models in a more structured and market-oriented manner. Program pemberdayaan ibu-ibu rumah tangga di desa Glagaharum bertujuan untuk mengatasi masalah keterbatasan pengetahuan bisnis yang dimiliki oleh kalangan ibu-ibu yang memiliki kemampuan untuk menjahit. Melalui pemberian edukasi pengetahuan business model canvas, diharapkan bahwa ibu-ibu yang mengikuti pelatihan ini dapat merancang bisnis mereka sendiri secara mandiri dan efektif. Kegiatan ini diawali dengan pemberian pre-test kepada 8 orang ibu-ibu peserta dilanjutkan dengan proses identifikasi proposisi nilai dari setiap ibu-ibu, lalu penjelasan daripada setiap elemen yang ada pada business model canvas seperti segmen pelanggan, proposisi nilai, saluran distribusi, hubungan dengan pelanggan, sumber daya utama, aktivitas kunci, mitra utama, sumber pendapatan, dan struktur biaya. Hasil dari program ini dapat dilihat dengan hasil pemberian post-test yang memiliki peningkatan nilai daripada pre-test. Ditambah ibu-ibu peserta kegiatan pada pertemuan tersebut sudah dapat merancang dan menyusun model bisnis mereka masing-masing dalam business model canvas. Sehingga dapat disimpulkan bahwa kegiatan ini menunjukkan adanya peningkatan pemahaman dari ibu-ibu dalam pengetahuan bisnis dan diharapkan bahwa ibu-ibu peserta dapat merancang model bisnis mereka dengan lebih terstruktur dan berorientasi terhadap pasar.